2014
DOI: 10.15407/cryo24.02.132
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of peptides in extracts of cryopreserved fragments of pig and piglet organs and role of endogenous proteases in their formation

Abstract: Реферат: Одним із підходів до проблеми корекції порушень функцій організму є створення лікарських засобів на основі біологічно активних пептидів. Нами розроблено метод одержання таких пептидів, який включає в себе процес кріоконсер-вування фрагментів органів. Досліджено концентрацію пептидів у екстрактах, одержаних із некріоконсервованих та кріо-консервованих фрагментів органів свиней та поросят, залежно від використаного кріопротектора та часу інкубації, а також визначена роль ендогенних протеаз в утворенні п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It was shown that the application of cryobiological techniques when obtaining the extracts from organ fragments of pigs and piglets allows to increase the yield and biological activity of peptides which containing in them (Rohoza et al, 2014a). There were matched the data obtained by MALDI-ToF method about the molecular masses of peptides in the extracts of cryopreserved fragments of piglets' skin and heart with the known peptides from the Protein Knowledgebase (UniProtKB) (Rohoza et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the application of cryobiological techniques when obtaining the extracts from organ fragments of pigs and piglets allows to increase the yield and biological activity of peptides which containing in them (Rohoza et al, 2014a). There were matched the data obtained by MALDI-ToF method about the molecular masses of peptides in the extracts of cryopreserved fragments of piglets' skin and heart with the known peptides from the Protein Knowledgebase (UniProtKB) (Rohoza et al 2014b).…”
Section: Introductionmentioning
confidence: 99%